2021
DOI: 10.3389/fpsyt.2021.730388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigation on the Impact of Cannabis Abuse on Thyroid Hormones and Associated Psychiatric Manifestations in the Male Population

Abstract: Cannabis abuse is a common public health issue and may lead to considerable adverse effects. Along with other effects, the dependence on cannabis consumption is a serious problem which has significant consequences on biochemical and clinical symptoms. This study intends to evaluate the harmful effects of the use of cannabis on thyroid hormonal levels, cardiovascular indicators, and psychotic symptoms in the included patients. This prospective multicenter study was conducted on cannabis-dependent patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(63 reference statements)
0
5
0
2
Order By: Relevance
“…Despite this, there are limited human data regarding the effects of cannabis on thyroid hormone levels. Two previous studies found lower TSH and T3 levels in acute cannabis users ( Malhotra et al., 2017 ; Parshad, Kumar & Melville, 1983 ), but these changes were not seen in chronic users ( Bonnet, 2012 ) or in cannabis-related psychosis patients ( Muzaffar et al, 2021 ). In our study, we found that FEP patients with a positive cannabis test in urine at admission had higher FT4 concentrations, although they maintained similar TSH concentrations than FEP patients with a negative cannabis test.…”
Section: Discussionmentioning
confidence: 88%
“…Despite this, there are limited human data regarding the effects of cannabis on thyroid hormone levels. Two previous studies found lower TSH and T3 levels in acute cannabis users ( Malhotra et al., 2017 ; Parshad, Kumar & Melville, 1983 ), but these changes were not seen in chronic users ( Bonnet, 2012 ) or in cannabis-related psychosis patients ( Muzaffar et al, 2021 ). In our study, we found that FEP patients with a positive cannabis test in urine at admission had higher FT4 concentrations, although they maintained similar TSH concentrations than FEP patients with a negative cannabis test.…”
Section: Discussionmentioning
confidence: 88%
“…There is positive relationship among anxiety and social adjustment of blind adolescent. Blind adolescents who experience the severe anxiety, in these blind adolescents, level of psychological well-being and social adjustment in society were low furthermore; those had low anxiety so there was higher level of psychological well-being and social adjustment [15]. Results indicate that there was 0.219 R value and value of R square was 0.048 (p < 0.05) which indicated that 4.8% of the variance in adjustment can be explained by a change in anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…They face certain stressors such as peer pressure, environmental demands; social and emotional difficulties and these problems directly affect their wellbeing [18]. If they are unable to cope up with these stressors then they are most likely to experience anxiety and suffer from mental issues (i.e., interpersonal problems, aggression, low confidence and less self-esteem), which may cause more deterioration in their overall adjustment [15,19].…”
Section: Discussionmentioning
confidence: 99%
“…Como único antecedente personal relevante en el caso, se encuentra el consumo diario de Cannabis sativa. Si bien no existe gran evidencia científica al respecto, los estudios publicados sobre la relación de los derivados de tetrahidrocannabinol y las hormonas tiroideas no han encontrado asociación alguna, así como tampoco parece ser un factor predisponente para la aparición de enfermedades tiroideas (15,16).…”
Section: Discussionunclassified